Effects of Successively Transmitted Verbal Descriptions on a Two-Response Sequence. - Okouchi, Hiroto (Psychological Record, 2023)
The present experiment examined the effects of instructions transmitted across more than two individuals on a two-response sequence. An undergraduate (participant) was exposed to a contingency of continuous reinforcement of touching two of eight squares in a specified sequence (i.e., touching first the upper-left square then the bottom-left square) presented on a computer touch screen. Then the participant was asked to describe how to obtain the reinforcers. The first participant's descriptions were presented to the next participant as instructions, prior to their exposure to the same contingency. In this way, verbal descriptions generated by each participant were transmitted from 1 participant to the next among 36 participants. Rates and percentages of the two-response sequence for the last 20 participants were higher than those for participants who were exposed to the contingency with no instructions (no instruction participants) and those who received descriptions generated by the no instruction participants. These results extend the generality of the effects of transmitted instructions on human responding, obtained from a multiple fixed-ratio differential-reinforcement-of-low-rate schedule in a previous experiment, to a continuous reinforcement schedule of a two-response sequence. Furthermore, they isolate the effects of instructions transmitted across more than two individuals from those transmitted within dyads.